Bivariate Analysis of the Correlation Between Determinants of Stunting in Toddlers - Lely Wahyuniar; Kusiyono Kusiyono (Ann Publisher, 2026)
Background. Stunting is a persistent dietary issue that significantly affects physical growth, cognitive development, and future productivity in children. Aims. This study is to examine the correlation between many variables and the prevalence of stunting in toddlers aged 6–59 months in Pekalipan Village, Cirebon City in 2025. Methods. The research methodology employs an analytical design utilizing a bivariate approach. The association between independent variables (maternal education, maternal age, birth weight, exclusive breastfeeding, immunization completeness, history of infectious diseases, and feeding patterns) and the dependent variable (stunting) was analyzed using the Chi-square test and Odds Ratio (OR) calculations. Result. The findings indicated a significant correlation between maternal education (p=0.027), maternal age at childbirth (p=0.007), birth weight (p=0.015), exclusive breastfeeding (p=0.028), history of infectious diseases (p=0.036), and feeding patterns (p=0.018) with the prevalence of stunting in toddlers. Simultaneously, full immunization did not demonstrate a significant correlation with stunting (p=0.382). Conclusion. This study concludes that stunting is affected by multiple maternal, perinatal, and parenting factors; therefore, prevention strategies must be comprehensive, focusing on enhancing maternal education, ensuring nutritional adequacy during pregnancy, preventing infectious diseases, and adopting suitable feeding practices.